Deviation between employee behaviors at MITC with the actual organizational behaviors / Nurdiyana Mohd Hashim - Mohd Hashim, Nurdiyana (Faculty of Business and Management, 2009)
My research focuses on the behavior and attitude among the employees and manager in the MITC organization. This behavior will effect the organization directly or indirectly. There are many excellent reasons behind studying this field, and I was elucidating some of them. Firstly, for organizational behavior and human performance. That is, the interrelationship between performance and the behavior of the employees can never be overemphasized. Secondly is problem solving. Most manager will term human behavior and reactions and actions as their major problems. These could range from poor performance, to lack of motivation, and lack of leadership among others. Thirdly, is dealing with organizational change. If changes are implemented in any organization, without taking into consideration the organizational behavior theories and studies, then the change may not be very effective. Lastly, is understanding actions and reactions. OB studies have develop many theories of how people act and react in a certain manner. For mangers and also for colleagues in a workplace it is important to be able to anticipate actions, and to be able to deal with reactions in most situation. Based on the result get from the analysis, most of the MITC staff are lack of the motivation on the self behavior toward organization and also community. MITC staff behavior is influence by the salary that provides by company, leadership strategy use by company and also the training program provide by company. They often to meet up with their top management for the work purpose compare the personal matter. They also can cooperate with other department for all time without complication matter. The organizational behavior also will affect their health in term of stress Regarding to the motivation, there do not enough motivation, that because of the less of satisfaction that provide by organization. The organization also is lack or leadership strategy to influence staff to work very well.